IMPLEMETASI PEMBELAJARAN BERBASIS PROYEK PADA BIDANG KEJURUA - Herminarto Sofyan (LPMPP Universitas Negeri Yogyakarta, 2006)
Vocational education is oriented to the formation ofprofessional competency. Such competency has to be supported bynn1 ':l't1